Fracturing Patriarchal Objectivity through Electro-Pop: Purity Ring and the vicissitudes of sight - Watkinson, Philip (Performance Research, 2021)
This article examines the deviated modes of seeing in the work of Canadian electro-pop band Purity Ring. Bringing their recent music into conversation with the theory of Tim Ingold and Eugenie Brinkema, I suggest that Megan James and Corin Roddick perform seeing as a granular, augmented act that continually shapes the boundaries between our bodies and the world around us. Particular attention is paid to James and Roddick’s creative engagement with optical touch and the formal capability of music to engage affectively with the act of seeing.By integrating musical examples, Tallulah Fontaine’s artwork for the band and the poetry of Kiran Millwood Hargrave, this article offers an expanded reading experience that spans the textual, the aural and the visual. I argue that the political crux of Purity Ring’s performance of perception lies in them moving beyond a reactionary response to patriarchal objectivity and towards a creative refiguration of perception as a form of subjectivation. The eyes that Purity Ring instantiate do not passively observe the world; they change it, both consoled and engulfed by the vicissitudes of perception.